SCAPS simulation of P3HT: graphene nanocomposites-based bulk-heterojunction organic solar cells / Nur Shakina Mohd Shariff, Puteri Sarah Mohamad Saad and Mohamad Rusop Mahmood - Mohd Shariff, Nur Shakina; Mohamad Saad, Puteri Sarah; Mahmood, Mohamad Rusop (UiTM Press, 2016)
The discovery of bulk-heterojunction concept and conjugated polymer led to an increasing interest towards organic solar cells. Eventhough organic solar cells are less expensive than inorganic solar cells, the power conversion energy is still considered low. This research’s main objective is to study the thickness and concentration effect of P3HT’s layer towards the efficiency of the P3HT:Graphene solar cells. SCAPS is a simulation software that is used in this research to simulate the effect on the solar cells. The solar cell’s structure is drawn in the simulation software and the parameters for each layers is inserted. From the overall results, the thickness of 100nm and the concentration of 1.0 x 1016 cm-3 yeild the optimum efficiency.